2013
DOI: 10.1002/bit.25147
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic tellurium nanorods as a novel antivirulence agent inhibiting pyoverdine production in Pseudomonas aeruginosa

Abstract: While antibiotic resistance in bacteria is rapidly increasing, the development of new antibiotics has decreased in recent years. Antivirulence drugs disarming rather than killing pathogens have been proposed to alleviate the problem of resistance inherent to existing biocidal antibiotics. Here, we report a nontoxic biogenic nanomaterial as a novel antivirulence agent to combat bacterial infections caused by Pseudomonas aeruginosa. We synthesized, in an environmentally benign fashion, tellurium nanorods (TeNRs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 53 publications
(56 reference statements)
5
27
0
Order By: Relevance
“…The same antibacterial properties were then reported using Te nanostructures against S. aureus, P. aeruginosa, Salmonella enterica serovar Typhi, and Klebsiella pneumoniae (37). Moreover, recently an interesting observation was made by Mohanty and colleagues (38), who reported that tellurium nanorods possessed antivirulence properties against P. aeruginosa and were able to effectively inhibit the production of pyoverdine, one of the main virulence factors in this bacterium. The exact mechanism of action of tellurium nanorods remains unclear.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The same antibacterial properties were then reported using Te nanostructures against S. aureus, P. aeruginosa, Salmonella enterica serovar Typhi, and Klebsiella pneumoniae (37). Moreover, recently an interesting observation was made by Mohanty and colleagues (38), who reported that tellurium nanorods possessed antivirulence properties against P. aeruginosa and were able to effectively inhibit the production of pyoverdine, one of the main virulence factors in this bacterium. The exact mechanism of action of tellurium nanorods remains unclear.…”
Section: Discussionsupporting
confidence: 57%
“…6). Similar noncytotoxic properties were observed with tellurium nanorods against human bronchial epithelial cells and murine macrophages (38). Additional experiments are under way to determine the effectiveness of the TeNSs against other, different bacterial species and to confirm their apparent nonnoxious properties against mammalian cells.…”
Section: Discussionsupporting
confidence: 55%
“…The versatility of Shewanella sp. extended to other metal electron acceptors, such as uranium, chromium, silver and even the reduction of nitro-aromatic compounds and tellurite [2][3][4][5][6]. Moreover, the production of sulphide and the reduction of elemental sulphur was also a special property of Shewanella genus.…”
Section: Introductionmentioning
confidence: 99%
“…Protein quantification was performed using BCA assay. The iTRAQ-based proteomic analysis was conducted as mentioned elsewhere (Mohanty et al 2013). …”
Section: Proteomic Analysismentioning
confidence: 99%
“…The RNA concentration was determined using Nanodrop spectrophotometer (Thermoscientific, DE, USA). The qPCR reactions and the data analysis were conducted as described elsewhere (Mohanty et al 2013). The primers used in qPCR are shown in Table S1.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%